Multicenter randomized trial of cerclage for preterm birth prevention in high-risk women with shortened midtrimester cervical length - OWEN, John (2009)
OBJECTIVE: To assess cerclage to prevent recurrent preterm birth in women with short cervix. STUDY DESIGN: Women with prior spontaneous preterm birth <34 weeks were screened for short cervix, and randomly assigned to cerclage if cervical length was <25 mm. RESULTS: Of 1014 women screened, 302 were randomized; 42% of women not assigned and 32% of those assigned to cerclage delivered <35 weeks (p=0.09). In planned analyses, birth <24 weeks (p=0.03) and perinatal mortality (p=0.046) were less frequent in the cerclage group. There was a significant interaction between cervical length and cerclage. Birth <35 weeks (p = 0.006) was reduced in the <15 mm stratum with a null effect in the 15–24 mm stratum. CONCLUSION: In women with a prior spontaneous preterm birth <34 weeks and cervical length <25 mm, cerclage reduced previable birth and perinatal mortality but did not prevent birth <35 weeks, unless cervical length was <15 mm.